Heavy metal contamination of drinking water in the city of Baiji - Sami. A. Zbaar; Shaker M. Marbut (Journal of Madenat Alelem University College, 2009)
In order to ascertain water quality for human consumption and determined the sources of contamination, heavy metal were evaluated in the drinking water supplies to the city of Baji and its surrounding villages in Iraq. Standard methods were used for determining the concentration of heavy metals include Pb , Cd, Cu, and Zn in drinking water samples by atomic absorption spectrophotometer supplied with a carbon rode atomizer to increase the sensitivity. The results showed that the amount of lead present in the drinking water is high and ranges from 0.06± 0.03 to 0.14± 0.02 ppm , cadmium value were from the below detection limit to 0.01 ppm, copper value were ranges from 0.21± 0.08 to 0.58± 0.04 and zinc value were ranges from 1.57 ±0.37 to 2.30±o.45. to investigate the sources of contamination a samples from waste water of Baiji refineries and Baji power station have been taken to measures Pb , Cd, Cu, and Zn contents. No correlations were found between metal concentrations in the drinking water samples. This means that the contamination might come from corrosion of the pipes line system.